Methodology of Hadith Research: The Study of Hadith Criticism - Rohman, Thofiqur; Huda, Ulul; Hartono, Hartono (Journal of Hadith Studies, 2019)
This paper is focused on the theme of hadith research methods. The focus of the theme of this hadith research method is the study of hadith criticism. Study of hadith criticism becomes important as this branch of science give contribution on how to figure out which are da'eef, fake, and authentic hadiths. This is because authentic Hadith takes fundamental part as the companion of Qur'an in learning Islam. Hadith criticism has meaning as a series of methods chosen by the hadith experts consciously to achieve validity degree of hadith. The purpose of hadith criticism is to contribute strong evidence that the traditions examined were really sourced from the Messenger of Allah. The method was born and developed since the Apostle PBUH, is still alive until now. The scope of study of hadith criticism covers the area of Sanad and Matn. In such an important way the science of hadith criticism, then places that knowledge in the priority position of the reviewer of the validity of the hadith.